THE EVOLUTION OF CIRCULAR ECONOMY FINANCING CONCEPTS IN THE SUSTAINABLE DEVELOPMENT PARADIGM. - Isamuxamedov Boxodir Baxramovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
In the context of increasing environmental constraints and growing systemic risks to sustainable development, the transformation of financial mechanisms to support the circular economy is of strategic importance. The aim of this study is to identify patterns and stages in the evolution of circular economy financing concepts within the sustainable development paradigm, as well as to justify their institutional and instrumental transformation.